Age-dependent shift in macrophage polarisation causes inflammation-mediated degeneration of enteric nervous system. Issue 5 (21st February 2017) - Becker, Laren; Nguyen, Linh; Gill, Jaspreet; Kulkarni, Subhash; Pasricha, Pankaj Jay; Habtezion, Aida
Abstract : Objective: The enteric nervous system (ENS) undergoes neuronal loss and degenerative changes with age. The cause of this neurodegeneration is poorly understood. Muscularis macrophages residing in close proximity to enteric ganglia maintain neuromuscular function via direct crosstalk with enteric neurons and have been implicated in the pathogenesis of GI motility disorders like gastroparesis and postoperative ileus. The aim of this study was to assess whether ageing causes alterations in macrophage phenotype that contributes to age-related degeneration of the ENS. Design: Longitudinal muscle and myenteric plexus from small intestine of young, mid-aged and old mice were dissected and prepared for whole mount immunostaining, flow cytometry, Luminex immunoassays, western blot analysis, enteric neural stem cell (ENSC) isolation or conditioned media. Bone marrow derived macrophages were prepared and polarised to classic (M1) or alternative (M2) activation states. Markers for macrophage phenotype were measured using quantitative RT-PCR. Results: Ageing causes a shift in macrophage polarisation from anti-inflammatory 'M2' to proinflammatory 'M1' that is associated with a rise in cytokines and immune cells in the ENS. This phenotypic shift is associated with a neural response to inflammatory signals, increase in apoptosis and loss of enteric neurons and ENSCs, and delayed intestinal transit. An age-dependent decrease in expression of the transcription factor FoxO3, a known longevity gene, contributes to the loss of anti-inflammatory behaviour in macrophages of old mice, and FoxO3-deficient mice demonstrate signs of premature ageing of the ENS. Conclusions: A shift by macrophages towards a proinflammatory phenotype with ageing causes inflammation-mediated degeneration of the ENS.